Auditing & assurance services / Timothy J. Louwers, James Madison University, David H. Sinason, Northern Illinois University, Jerry R. Strawser, Texas A&M University, Jay C. Thibodeau, Bentley College, Allen D. Blay. - Blay, Allen D.
Mua